Protein and fatty acid profile of marine fishes from Java Sea, Indonesia - SRI PRIATNI; DIAH RATNANINGRUM; WAWAN KOSASIH; EEN SRIENDAH; YOICE SRIKANDACE; TINA ROSMALINA; SRI PUDJIRAHARTI (Society for Indonesian Biodiversity, 2018)
Priatni S, Ratnaningrum D, Kosasih W, Sriendah E, Srikandace Y, Rosmalina T, Pudjiraharti S. 2018. Protein and fatty acid profile of marine fishes from Java Sea, Indonesia. Biodiversitas 19: 1737-1742. Indonesia is the second largest producer of capture fisheries products in the world and the most capture fisheries production comes from marine fisheries. Marine fish is a source of protein, amino acid, saturated and unsaturated fatty acids, which are important components of diet. The objective of the study was to investigate the protein and fatty acids profile of nine marine fish samples from Java Sea of Indramayu West Java, Indonesia. The analysis data showed that the total protein content of fish samples ranged from 61.07% (Pampus argenteus) to 86.56% (Tetraodontidae). Meanwhile, total lipid content of fish samples ranged from 1.73% (Tetraodontidae) to 9.82% (Leiognathus equulus). The concentration of ?-Amino Nitrogen (AN) of fish protein hydrolysate was ranging from 31 mM (Nemipterus hexodon) to 69 mM (Mystacoleucus padangensis) and% Degree of Hydrolysis (DH) was ranging from 9.33% to 20.39%. The molecular weight of protein fish samples had similar profiles primarily for almost all samples, which could be observed from a typical band with the weight around 49 kDa. The saturated fatty acid (? SFA) compositions of fish species ranged from 1094.03-4233.03 µg/g. Oleic acid (MUFA) content of all fish species ranged from 257.91-1216.06 µg/g. However, only three fish species contain of Poly Unsaturated Fatty Acid (PUFA) linoleic acid as the following; Selaroides leptolepis (171.36 µg/g), Oxyeleotris marmorata (249.40µg/g) and Tetraodontidae (140.35 µg/g). The highest SFA content was found in S. leptolepis with palmitic acid (C16:0) as the dominant saturated fatty acid (2320.88 µg/g). S. leptolepis also contained high oleic acid (1216.06 µg/g) and linoleic acid (171.36 µg/g).